A graphene hybrid supramolecular hydrogel with high stretchability, self-healable and photothermally responsive properties for wound healing. Issue 11 (4th February 2021) - Zhang, Haifeng; Zheng, Shiya; Chen, Canwen; Zhang, Dagan
Abstract : The hydrogel demonstrated properties with high stretchability, self-healable and photothermal properties. Notably, photothermal therapy could be established due to its photothermal responsiveness, benefiting infected wound healing. Abstract : Wound healing is a ubiquitous healthcare problem in clinical wound management. In this paper, the fabrication of a graphene hybrid supramolecular hydrogel (GS hydrogel) for wound dressing applications is demonstrated. The hydrogel is composed of two components, including N -acryloyl glycinamide (NAGA) as the scaffold and graphene as the photothermally responsive active site for photothermal therapy. Based on the multiple hydrogen bonds between the dual amide motifs in the side chain of N -acryloyl glycinamide, the hydrogel exhibits high tensile strength (≈1.7 MPa), good stretchability (≈400%) and self-recoverability. In addition, the GS hydrogel shows excellent antibacterial activity towards methicillin-resistant Staphylococcus aureus (MRSA), benefiting from the addition of graphene that possesses great photothermal transition activity (≈85%). Significantly, in vivo animal experiments also demonstrated that the GS hydrogel effectively accelerates the wound healing processes by eradicating microbes, promoting collagen deposition and angiogenesis. In summary, this GS hydrogel demonstrates excellent mechanical performance, photothermal antimicrobial activity, and promotes skin tissue regeneration, and so has great application potential as a promising wound dressing material in clinical use.